Exacerbations of Chronic Obstructive Pulmonary Disease and Cardiac Events. A Post Hoc Cohort Analysis from the SUMMIT Randomized Clinical Trial - Kunisaki, Ken M. (Am J Respir Crit Care Med, 2018)
Rationale: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are common, associated with acute inflammation, and may increase subsequent cardiovascular disease (CVD) risk. Objectives: Determine whether AECOPD events are associated with increased risk of subsequent CVD. Methods: We performed a secondary cohort analysis of the SUMMIT (Study to Understand Mortality and Morbidity) trial, a convenience sample of current/former smokers with moderate COPD from 1,368 centers in 43 countries. All had CVD or increased CVD risk. AECOPD was defined as an increase in respiratory symptoms requiring treatment with antibiotics, systemic corticosteroids, and/or hospitalization. CVD events were a composite outcome of cardiovascular death, myocardial infarction, stroke, unstable angina, and transient ischemic attack. All CVD events were adjudicated. Cox proportional hazards models compared the hazard for a CVD event before AECOPD versus after AECOPD. Measurements and Main Results: Among 16,485 participants in SUMMIT, 4,704 participants had at least one AECOPD and 688 had at least one CVD event. The hazard ratio (HR) for CVD events after AECOPD was increased, particularly in the first 30 days after AECOPD (HR, 3.8; 95% confidence interval, 2.7–5.5) and was elevated up to 1 year after AECOPD. The 30-day HR after hospitalized AECOPD was more than twofold greater (HR, 9.9; 95% confidence interval, 6.6–14.9). Conclusions: In patients with COPD with CVD or risk factors for CVD, exacerbations confer an increased risk of subsequent CVD events, especially in hospitalized patients and within the first 30 days after exacerbation. Patients and clinicians should have heightened vigilance for early CVD events after AECOPD. Clinical trial registered with www.clinicaltrials.gov (NCT 01313676).